Gambaran Sikap Penjamah Makanan Tentang KeamananPangan Di Rumah Makan Taman Sari Colomadu Karanganyar - Karo, Afrianus, Luluk Ria Rakhma, S.GZ,M, Endang Nur W, SST,M.Si.Med (2016)
Introduction: Food Insecure can cause a disease called foodborne diseases. Lack of concern about food hygiene by food handlers actors will have an impact on the quality of the food was presented. Some incidence of disease caused by food consumed was contaminated by pathogenic bacteria Purpose: This study aimed to describe the attitude of the food handlers about the safety of eating while preparing food Methods: This study was observational research Deskriptiv. Research instrument used was a questionnaire about the attitude of the food handlers on food safety. These samples included 28 people (total sampling) Result : Based on this research, the sample karakteristk educational level known as much as 53.57% of the workers are high school graduates, junior high as 35.71% and 10.71% of graduates from elementary school. Lifespan of most food handlers are aged 25 years or older with a percentage of 57.14% while those less than 25 years is as much as 42.85%. The observation of the total processing power of food in a restaurant garden sari 100% are women. The tenure of the food handlers at restaurants garden sari mostly less than five years as many as 23 people with a total percentage of 82.14% and working between 5-10 years of 5 people with a percentage of 17.85%. and the results of the study found that 71.42% of food handlers stance classified with a good attitude, 17.85% had a moderate attitude and as much as 10.71% have less attitude. Conclusion: Based on data collection sample karakteristk education can be seen as much as 57% are high school graduates, age most are 25 years and above with a total percentage of 57.14%, processing power all women. A total of 71.42% handlers have a good attitude about food safety Suggestion: It is necessary to increase the training terhdap attitude handlers such as courses, training, since there are no processing power is being poor and need the awareness of each person involved in the food menagement to always pay attention to food safety